2020
DOI: 10.3390/antiox9090813
|View full text |Cite
|
Sign up to set email alerts
|

The Sorbus spp.—Underutilised Plants for Foods and Nutraceuticals: Review on Polyphenolic Phytochemicals and Antioxidant Potential

Abstract: The Sorbus spp. are valuable plants, which have been used for ornamental purposes, in traditional medicines and less seldom in foods. Recent studies have revealed different anatomical parts of the Sorbus spp. to contain valuable phytochemicals demonstrating various bioactivities. However, in terms of applications in the products intended for human consumption, Sorbus still remains as an underutilised genus. The increasing number of studies on phytochemicals, antioxidant potential and other bioactivities of Sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(96 citation statements)
references
References 98 publications
1
91
0
4
Order By: Relevance
“…Several studies have demonstrated the importance of service tree fruits as a good source of different bioactive phytochemicals [ 26 , 41 , 58 , 59 ]. It was reported that those constitutes are mostly affected by geographic origin and genotype [ 26 , 60 ], climatic environment [ 61 , 62 , 63 ], and stage of maturity [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of service tree fruits as a good source of different bioactive phytochemicals [ 26 , 41 , 58 , 59 ]. It was reported that those constitutes are mostly affected by geographic origin and genotype [ 26 , 60 ], climatic environment [ 61 , 62 , 63 ], and stage of maturity [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the quality characteristics of rowanberries, Bussinka, Vefed, and Solnechnaja were rich in vitamin C content, while the latter two were also not astringent [12]. Moreover, previous investigations have reported the antioxidant capacity [3] and bacteriostatic effect [13] of both wild and cultivated rowanberry extracts. Considering the diverse genetic background of sweet rowanberry cultivars, there is no comprehensive information available about the antioxidant properties and phenolic content of these fruit, juice, and pomace.…”
Section: Introductionmentioning
confidence: 99%
“…Davon wachsen ca. 35 Arten im Kaukasus und in der Türkei, 91 in Europa, 111 in China, Vietnam, Myanmar und im Himalaya [27], [28]. Im engeren Sinne gehören etwa 88 Arten zu dieser Gattung [28].…”
Section: Verbreitung Und Botanikunclassified